Implementación de las bellas artes en la enseñanza de segundas lenguas, La - Dorado-Budia, Manuel, author; Suárez-García, José Luis, advisor; Purdy, Andrea, committee member; Prince, Eric, committee member (Colorado State University. Libraries, 2016)
Throughout the late decades of the twentieth century and early twenty-first century, the concept of how a language should be taught has changed significantly in response to different aspects of it, and it paying special attention to the various needs of each individual in class. In an era in which learning and teaching theory are urging the educational community the integration of different academic disciplines, it is not surprising that the role of fine and performing arts in language learning appears as a key and innovative reason to engage our students in the classroom. It is, therefore, the result of the combination between language and the arts that matters, applying the knowledge of a language to the culture that radiates each of the artistic disciplines, so that students, not only learn the linguistic and grammatical elements but also are capable to know and understand cultural aspects in a transverse way, develop creativity and open their minds to a new world. For all these reasons, the interest of this thesis lies in being aware of which are the connections between the use of artistic areas and the acquisition of a second language, as well as the benefits of its use in language teaching, obtaining better and more satisfactory results.
Text in Spanish; title and abstract in English and Spanish.